Technology News - No. 468 - Tests of Doppler Radar Technology for Haulage Truck Backup Alarms (The National Institute for Occupational Safety and Health (NIOSH), 1997)
Reduce haulage truck accidents resulting from blind spots, with a special emphasis on reducing accidents during backing operations.